2013
DOI: 10.1093/carcin/bgt063
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes hepatocellular carcinoma cell invasion through activation of epithelial–mesenchymal transition

et al.

Abstract: Ubiquitin-conjugating enzyme E2 J2 (UBE2J2) is an ubiquitin proteasome component that responds to proteotoxic stress. We found that UBE2J2 was highly expressed in cellular protrusions of HCCLM3 metastatic hepatocellular carcinoma (HC) cells. Immunohistochemical analyses showed that UBE2J2 was expressed at higher levels in HC patient tissues than in corresponding non-tumor tissues. Because cellular protrusions are important for cell invasion, we hypothesized that UBE2J2 promotes HC cell invasion. We used chip-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
217
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(231 citation statements)
references
References 36 publications
9
217
0
1
Order By: Relevance
“…18,40 Some new studies have revealed the close relationship between autophagy and the EMT. For example, Li et al 16 report that starvation-induced autophagy is critical for cellular invasion through induction of the EMT in hepatocellular carcinoma cells. Furthermore, in breast carcinoma, Akalay et al 41 show that EMT-induced tumor cell resistance to cytotoxic Tlymphocytes (CTLs) is correlated with the induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,40 Some new studies have revealed the close relationship between autophagy and the EMT. For example, Li et al 16 report that starvation-induced autophagy is critical for cellular invasion through induction of the EMT in hepatocellular carcinoma cells. Furthermore, in breast carcinoma, Akalay et al 41 show that EMT-induced tumor cell resistance to cytotoxic Tlymphocytes (CTLs) is correlated with the induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma cells, starvationinduced autophagy is critical for cellular invasion through induction of the EMT. 16 Furthermore, in mouse models of pulmonary metastasis of hepatocellular carcinoma cells, inhibition of autophagy has been shown to significantly decrease the incidence of pulmonary metastases in vivo. 17 Inhibition of autophagy via knockdown of autophagy related 12 (ATG12) in glioma cells does not affect cell viability, proliferation, or migration, but significantly reduces cellular invasion in a 3-dimensional (3D) organotypic model.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports demonstrated that autophagy was involved in the EMT progress of some cell lines or tumor tissues, [39][40][41][42] and the embryonic EMT was similar to the transformation of cell phenotype during carcinoma progression. 43 Thus, we did perform the evaluation of E-Cadherin, N-Cadherin and laminin expression following the treatment of RAPA and 3-MA (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1). In combination with other recent studies showing a role for autophagy in epithelial-to-mesenchymal transition (EMT) and tumor cell invasion, 5,10 this suggests that autophagy inhibition may reduce progression to invasive disease and metastatic dissemination by blocking tumor cell motility and invasion in patients with early non-disseminated disease, although this represents a small subset of patients given the difficulties of early detection in many solid tumor types. Moreover, the mechanism that we have identified likely represents the co-opting of a normal physiological function for autophagy through focal adhesion disassembly, adding to a growing body of literature indicating that the autophagy machinery has many functions beyond its classic role in promoting cellular homeostasis and survival.…”
mentioning
confidence: 75%